2001
DOI: 10.4314/zjh.v28i2.6763
|View full text |Cite
|
Sign up to set email alerts
|

Marriage as a survival strategy: The case of Masvingo, Zimbabwe

Abstract: ft is the contention of this article that marital hope and pursuit of the marital strategy functions as a suwival option for some female heads of households as shown in this study. This article examines how and in what ways female heads of households benefited or were disadvantaged by the lack of or entry into various forms of marital relationships. The experiences of many of the women interviewed for this study showed that the pursuit of the marital strategy had had different outcomes for different individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In this regard, male dominance and domestic violence colluded to render women powerless and therefore vulnerable. The vulnerability of married women to HIV and AIDS due to unequal power relations in marriage is well documented (Chitando, 2004; Chitando, 2011; Desai, 2005; Francisco, 2010; Mungwini, 2008; Muzvidziwa, 2001; Phiri, 2002). From some of the participants’ experiences, it can be noted that domestic violence and HIV and AIDS coexisted.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, male dominance and domestic violence colluded to render women powerless and therefore vulnerable. The vulnerability of married women to HIV and AIDS due to unequal power relations in marriage is well documented (Chitando, 2004; Chitando, 2011; Desai, 2005; Francisco, 2010; Mungwini, 2008; Muzvidziwa, 2001; Phiri, 2002). From some of the participants’ experiences, it can be noted that domestic violence and HIV and AIDS coexisted.…”
Section: Discussionmentioning
confidence: 99%
“…Formal marriages have the potential of exposing wives to HIV and AIDS infection because of the fact that the rights and obligations of married persons make it hard for parties to insist on safe sexual practices (Muzvidziwa, 2001;Chirawu, 2006;Chitando, 2004;ICASO, 2007). The husband feels empowered to have sex with his wife whenever he wants because he has paid lobola, and also because the marriage vows are seen as suggesting that the wife cannot refuse her husband sex, since sex is the essence of marriage.…”
Section: Monogamous Marriage As a Risk Factor Relative To Hiv And Aidsmentioning
confidence: 98%
“…This finding concurs with Muzvidziwa's (2001: 151) from a study conducted among women in informal marital unions (mapoto) in Masvingo town, Zimbabwe, where the mapoto women indicated that they were in a better situation than women in formal marriages who were "sitting ducks in the face of HIV/AIDS", and who could not insist on safe sexual practices as they themselves could. This was possible because the mapoto women continued to maintain a high degree of independence as far as decisions about their lives were concerned (Muzvidziwa, 2001).…”
Section: Monogamous Marriage As a Risk Factor Relative To Hiv And Aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single women were discriminated against in the allocation of trading space because of their marital status (Zhou, 1993 cited in Gaidzanwa, 1997: 162-163). The option of cross-border trading is a highly lucrative activity closed to the majority of women from rural areas as they lack cash and the formal documents required for these activities (Cheater and Gaidzanwa, 1996;Muzvidziwa, 2000Muzvidziwa, , 2001).…”
Section: Chaptermentioning
confidence: 99%